Unveiling the Legal Landscape: A Comprehensive Study on Motor Vehicle Insurance in Accordance with the Commercial Law Code - Dijan Widijowati (LifeSciFi, 2022)
The regulation of commercial insurance in Indonesia is governed by the Indonesian Civil Code, in which insurance is considered a contract subject to the same general principles as other contractual agreements. Furthermore, the Insurance Law No. 2 of 1992 defines insurance as a business that regulates the conduct of those who operate insurance businesses. This research employs a qualitative approach using descriptive techniques to analyze motor vehicle insurance law according to the Indonesian Commercial Code. The findings suggest that insurance companies are institutions that collect funds from society and operate based on principles of responsible and healthy business practices, in accordance with government regulations. Responsibility is ensured through the issuance of insurance policies that outline the agreed-upon terms between the insurer and insured party, with the payment of premiums signifying the transfer of risk and the establishment of rights and obligations between the parties.